Studies on Stereoselective Synthesis of Functionalized Aliphatic Chains Containing Stereogenic Centers through the Pd(II)- Catalyzed C-H Activation - Gopalakrishnan, B. (IISERM, 2019)
The transition metal-catalyzed C(sp 3 )-H and C(sp 2 )-H functionalization is emerging as one of the important synthetic transformations for the construction of C–C and C–X bonds (X = C, N, O, P, etc.). This thesis work aimed to synthesize functionalized aliphatic chains containing stereogenic centers through the Pd-catalyzed directing group-aided diastereoselective C(sp 3 )-H functionalization/arylation strategy. Accordingly, the bidentate directing group 8-aminoquinoline- aided Pd(II)-catalyzed diastereoselective β-arylation of the prochiral secondary sp 3 C-H bonds of 2-phenylbutanamides and related aliphatic carboxamides was reported. Next, the diastereoselective sp 3 C−H arylation followed by ring opening of cyclopropanecarboxamides was reported. Further, bis-arylation of methyl sp 3 C-H bonds of racemic and optically pure 2-arylpropionamides and desymmetrization of symmetrical dicarboxylic acid systems via arylation of methylene sp 3 C-H bonds were reported.
Keywords: Metal-catalyzed; Dicarboxylic acid; Methylene; Bonds